Analytical Study of National Housing Finance Policies and Implementation Strategies Case Study: Baghdad Governorate (Journal of Planner and Development, 2022)
Housing finance is one of the main components of housing, and it is relied upon to help families buy, build, add building, and housing improve. Accordingly, different countries all over the world set policies and strategies for the purpose of organizing and developing the financial sector to solve quantitative and qualitative housing problems. This research aims to identify housing finance policies and strategies in Iraq and Baghdad governorate. The most prominent sources of housing financing are the Real Estate Bank and the Housing Fund, and accordingly the focus has been on the role of these two institutions in filling the housing need in the governorate. The ratio of the loan to the value of the house reached approximately 38%, which is a small percentage compared to the countries of the world, and the percentage of loan repayment installments is not commensurate with low-income people, especially employees among them. Despite the good role played by the Real Estate Bank and the Housing Fund, but the policy that these institutions lend to secondary (commercial) institutions is difficult to implement, due to the limited government allocations. Therefore the directing low-interest government funds to low-income households have not been implemented, and new regulations and instructions have not been proposed to increase affordability. So the role of commercial and Islamic banks to enter the real estate finance activity is still weak .